A formação do licenciado em Enfermagem no estado do Pará: as prescrições curriculares no período de 1977 a 2006 - ALENCAR, Mônica Florice Albuquerque (Universidade Federal do Pará, 2012)
This research aims to investigate what curriculum matrix, nursing and educator ‘s concepts and professional profiles that were used throughout the history of the curriculum of Full Degree Nursing in UFPA since its creation to the implementation of the Project Teaching Course. The problem lies in comprehension of the influences exerted by the economic, political and social environment on the proposed curriculum, considering the historical moment in which each was produced, the social actors who did and why they have done. This is a qualitative research in Social Sciences, the methodological approach employed an exploratory descriptive and historical and organizational case study, which was based on documentary research advised by interview technique. The results showed that as the historical moment lived by the Institution, the training of licensed nursing was more or less valuable, however, always present in the history curriculum of Full Degree Nursing in UFPA. The challenge adopted, exclusively in the context of Pará, reveals the commitment of the Institution to the quality of teacher education in nursing in Pará, whereas interest in perpetuating such mission.